2008
DOI: 10.1074/jbc.m802374200
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Neuroprotective Survival Signal in Mice Lacking Insulin Receptor Gene in Rod Photoreceptor Cells

Abstract: Insulin receptor (IR) signaling provides a trophic signal for transformed retinal neurons in culture, but the role of IR activity in vivo is unknown. We previously reported that light causes increased tyrosine phosphorylation of the IR in vivo, which leads to the downstream activation of the phosphoinositide 3-kinase and Akt pathway in rod photoreceptor cells. The functional role of IR in rod photoreceptor cells is not known. We observed that light stress induced tyrosine phosphorylation of the IR in rod photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
113
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(123 citation statements)
references
References 51 publications
9
113
1
Order By: Relevance
“…Supporting this hypothesis are the data that show deletion of Akt2, one of the isoforms of Akt, results in stress-induced photoreceptor degeneration ( 135 ). Furthermore, rod-specifi c IR knockout mice have reduced PI3K and Akt recruitment to the membranes, suggesting that the IR regulates the downstream PI3K and Akt survival signal in rod photoreceptors ( 148 ). The IR knockout mice exhibited no detectable phenotype when they were raised in dim cyclic light.…”
Section: Light-induced Activation Of Pi3k Pathway In Rod Photoreceptosupporting
confidence: 51%
See 3 more Smart Citations
“…Supporting this hypothesis are the data that show deletion of Akt2, one of the isoforms of Akt, results in stress-induced photoreceptor degeneration ( 135 ). Furthermore, rod-specifi c IR knockout mice have reduced PI3K and Akt recruitment to the membranes, suggesting that the IR regulates the downstream PI3K and Akt survival signal in rod photoreceptors ( 148 ). The IR knockout mice exhibited no detectable phenotype when they were raised in dim cyclic light.…”
Section: Light-induced Activation Of Pi3k Pathway In Rod Photoreceptosupporting
confidence: 51%
“…There are no direct studies available on the disruption of the p110 subunit of PI3K in retinal cells. However, our previous work demonstrated that PI3K activity in photoreceptors is regulated through the IR ( 148 ). Rod-specifi c IR knockout mice have reduced PI3K and Akt association with the membranes, suggesting that the IR regulates the downstream a new mechanism in which the PI3K/Akt cassette functions as a master regulator of cellular metabolism.…”
Section: Light-induced Activation Of Pi3k Pathway In Rod Photoreceptomentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of IR activation leads to neurodegeneration in brain/neuron-specific IR knock-out mice (14). We have previously reported that conditional deletion of IR in rod photoreceptor neurons resulted in a stressinduced photoreceptor degeneration (15).…”
mentioning
confidence: 99%